Exploring logical connectors in journals with different indexing levels: A comparison between international and national indexed journals - Kurniawan, Eri; Ruswan, Dallyono; Cahyowati, Avika (Indonesian Journal of Applied Linguistics, 2019)
Research to date has witnessed the mounting significance of logical connectors in writing including scientific journal articles; however, little is known as to whether the usage of such connectors may correspond to a varying degree of journal quality. This qualitative study fills in the void by exploring the use of logical connectors in journals with different indexing levels, national and international. Sixty articles were collected from two journals, thirty articles from each. Implicit behind this study is an assumption that differing journal indexing entails differing journal quality. Nineteen connectors that belong to the most frequently used conjunctive adverbials in academic prose were searched using Laurence Anthony’s concordance program (AntConc). The findings reveal that the top-two most frequently CAs used in both corpora are adversative however and causal therefore. Based on these results, the analysis is centered on these two CAs by investigating the coherence relations in order to see the underlying logical relationships between two sentences. The findings show that the illogical uses of CA however and therefore were equally found in both corpora although the percentages for the illogical use in the international journal articles are less than those in the national ones. In conclusion, not only do articles in the two journals share the same tendencies in the logical use, they also evince the same patterns of problem, namely failure in recognizing logical relationships and overuse of connectors. Of importance is that the purported relationship between journal indexation and logical use of connectors may be at best weak, and at worst absent, for both journals in question dominantly exhibit a logical usage of connectors. Pedagogical implications are also discussed.